Mantodea of Panguana (Insecta: Dictyoptera) - Schwarz, Christian J.; Ehrmann, Reinhard; Stiewe, Martin B.d.; Mörtter, Rolf; Falkenberg, Michael (Zootaxa, 2020)
We present here the first illustrated checklist of the praying mantids (Mantodea) collected at the Panguana Field Station in Central Peru over the course of 50 years. The examination of over 430 specimens obtained mainly by light-trapping, but also other methods, revealed 44 species in 28 genera. Mantoida brunneriana, Mantoida cf. argentinae, Pseudomiopteryx cf. decipiens, Angela trifasciata, Liturgusa neblina, Cardioptera squalodon, Metriomantis cf. pilosella, Acontista festae, and Heterovates pardalina are new Peruvian records. Microphotina panguanensis n. sp. is new to science and the first species of the genus Microphotina described from the Western Amazon. The checklist of confirmed Peruvian Mantodea species is raised to 80. Thus, more than half of the currently known Peruvian Mantodea species is found at Panguana. We discuss the reasons for this diversity and comment on putative additional species which might be sampled if collection efforts are intensified. The results highlight the Conservation value of ACP Panguana for Western Amazonian Mantodea.